(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: The ubiquitous nature of molds, their ability to colonize diverse substrates, and the lack of effective control measures have contributed to the high incidences of molds and mycotoxin contamination in foods and feeds. These dangerous secondary metabolites enter the food chain in the field, during storage, or later. Material and Methods: A total of 40 livestock feed samples were randomly collected from ten farms in eastern Algeria. The ten types of analyzed feed were: wheat bran, dried bread, alfalfa, straw, oat hay, barley, date scraps, grass silage, corn silage, and concentrate. Results and Discussion: Results show that all the samples were contaminated with different species of fungi. A total of 248 fungal strains were isolated. In terms of frequency, the genus Aspergillus was the most frequent fungi recovered from 32 samples (80%) between all feeds studied, followed by the genus Penicillium recovered from 31 samples (77.5%). Conclusion: As a preventive measure, appropriate agricultural practices could provide unfavorable conditions for the development of fungi and toxinogenesis. However, the installation of a mycotoxins-monitoring program may be necessary to protect animals' and consumers' health.